Recycling seltener Metalle: Ein Weg zuresilienten grünen Lieferketten - André Wolf (Wirtschaftsdienst, 2023)
Zukunftstechnologien, wie Elektromotoren und Windkraft-Turbinen, enthalten wertvolle selteneMetalle, deren Recycling einen wichtigen Schritt zu einer grünen Kreislaufwirtschaft darstellenwürde. Doch ein Aufbau von Lieferketten für recycelte Metalle ist mit Schwierigkeiten, wiemangelnder technischer Standardisierung, geringer Sammelquoten von Altprodukten undniedriger Effizienz von Recycling-Technologien konfrontiert. – – Green technologies, like electric motors, contain valuable rare metals. Recycling these would represent an important steptowards a green circular economy. However, the development of supply chains for recycled metals faces difficulties such as a lack oftechnical standardisation, low collection rates of end-of-life products and low efficiency of recycling technologies. European policymak-ers must address these obstacles by a targeted approach, combining requirements on data transparency and supply chain cooperationwith new support schemes to accelerate the upscaling of recycling capacities. An auction-based production premium for recyclers canhelp to overcome the funding gap in the early stages of capacity development.
Keywords: Q53; Q32; O33; 330; Kritische Metalle; Kreislaufwirtschaft; Lieferkette; Resilienz; Kritische Metalle; Kreislaufwirtschaft; Lieferkette; Resilienz